Analysis Of Mean Time Between Failure (MTBF) On Oil Production Machines - Laksono, Eki Dipo (Sean Institute, 2025)
This study aims to analyze the effectiveness of engine maintenance based on the Mean Time Between Failures (MTBF) approach for Engine units A and B during the period from PM 1000 Hours to the end of May 2024. The data analyzed include failure times, shutdown durations, operating hours, and estimated production losses due to operational halts. The results show that Engine A experienced 10 failures with a total downtime of 87 hours, while Engine B experienced 16 failures with 68 hours of downtime. The total loss due to shutdowns throughout the observation period amounted to IDR 4.78 billion, while the potential production revenue loss reached approximately IDR 1.3 trillion. The findings also indicate that mid-interval maintenance is not necessary, as the associated losses are lower than the cost of repairs. This study recommends adopting the MTBF method to support preventive maintenance decisions in order to enhance operational efficiency and minimize financial losses